2014
DOI: 10.17221/161/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli isolated from lump sheep's cheeses and their antimicrobial properties

Abstract: Smetanková J., Hladíková Z., Zimanová M., Greif G., Greifová M. (2014): Lactobacilli isolated from lump sheep's cheeses and their antimicrobial properties. Czech J. Food Sci., 32: 152-157.A total of 34 strains of lactobacilli were isolated from the lump sheep's cheeses produced from raw sheep milk. The strains were identified by MALDI-TOF MS, and 20 of them demonstrating the best fermentation and sensoric properties in milk were chosen and tested for their antimicrobial activity. All selected strains were acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The microbiota in raw ewe milk is represented mainly by Lactobacillus spp., Enterococcus spp., Lactococcus spp., Streptococcus spp., Kluyveromyces marxianus, and Geotrichum candidum. [1,2,12,56] Descriptive sensory analysis performed on bryndza cheese samples demonstrated statistically significant influence of storage in NP and VP samples on the intensities of sensory descriptors of appearance: smooth paste and lumpy; descriptors of aroma: sour, ovine, yeasty, milk fat, dank, pungent, putrescent; descriptors of taste: delicious, sheep cheese taste, pleasantly acidic, salty, bitter, musty; and descriptors of consistency: spreadable, firm, cohesive, soft, sticky, curdy, and friable (p < 0.001). It has been reported that the use of modified atmosphere packaging for dairy products with high percentages of CO 2 may have a detrimental effect on the sensory properties, especially with regard to flavour.…”
Section: Parameter Storagementioning
confidence: 99%
“…The microbiota in raw ewe milk is represented mainly by Lactobacillus spp., Enterococcus spp., Lactococcus spp., Streptococcus spp., Kluyveromyces marxianus, and Geotrichum candidum. [1,2,12,56] Descriptive sensory analysis performed on bryndza cheese samples demonstrated statistically significant influence of storage in NP and VP samples on the intensities of sensory descriptors of appearance: smooth paste and lumpy; descriptors of aroma: sour, ovine, yeasty, milk fat, dank, pungent, putrescent; descriptors of taste: delicious, sheep cheese taste, pleasantly acidic, salty, bitter, musty; and descriptors of consistency: spreadable, firm, cohesive, soft, sticky, curdy, and friable (p < 0.001). It has been reported that the use of modified atmosphere packaging for dairy products with high percentages of CO 2 may have a detrimental effect on the sensory properties, especially with regard to flavour.…”
Section: Parameter Storagementioning
confidence: 99%
“…In the region of Slovakia, the time length of sheep cheese production season is approximately consistent with the time length of ewe lactation and grazing season, but the most important fact is that sheep grazing in specific mountain areas of Slovakia are fed on very diverse and unique vegetation, which gives the lump sheep cheese made from such milk a characteristic taste, aroma and specific microbiota (Smetanková et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…LAB produce a variety of protein hydrolases, including cell wall proteases, peptide transporter proteases, and sufficient intracellular peptidases, which are capable of biodegrading mycotoxins into less toxic and less harmful compounds [ 5 ]. Smetankova et al [ 54 ] observed that the mean inhibitory area of L. plantarum against A. flavus accounted for 10.4% of the total area, among which the antifungal compounds effective against A. flavus contained diacetyl. The antifungal mechanism of diacetyl may be due to the induction of ROS (reactive oxygen species) accumulation, which can disrupt the membrane structure and lead to leakage of cellular material and cell death [ 55 ].…”
Section: Introductionmentioning
confidence: 99%